Soil Animals and Pedogenesis: The Role of Earthworms in Anthropogenic Soils. Issue 3 (March 2016) - Cunha, Luis; Brown, George G.; Stanton, David W. G.; Da Silva, Elodie; Hansel, Fabricio A.; Jorge, Gabriella; McKey, Doyle; Vidal-Torrado, Pablo; Macedo, Rodrigo S.; Velasquez, Elena; James, Samuel W.; Lavelle, Patrick; et al.
Abstract : Abstract: The role of earthworms as one of the most important groups of ecosystem engineers in human-modified and natural environments has been increasingly recognized only during the last 30 years, yet earthworms and humans have been acting together in building landscapes for millennia. This relationship is well represented in the pre-Columbian raised fields, in flood-prone savannas around the rim of Amazonia, but also by the potentially significant role of earthworms in the formation and resilience of Amazonian Dark Earths. Through the bioturbating action of earthworms, soil is biologically, chemically, and physically altered; nutrients are translocated; organic matter is decomposed and transformed; and the surrounding biota interacts as a large orchestra where the soil musicians play together on the various instruments but where earthworms take a leading role, enhancing microbial activity and generally stimulating plant growth. In this article, we assess the remarkable role of earthworms at the center of soil pedogenetic processes within anthropogenic landscapes, dissecting their functions with a special focus on Amazonian Dark Earths. Abstract : Supplemental digital content is available in the text.